PERAN PENGURUS CABANG IPNU DALAM MENUMBUHKAN MINAT BERORGANISASI BERLANDASKAN NILAI-NILAI ASWAJA AN-NAHDLIYAH DI MADRASAH TSANAWIYAH HASYIM ASYARI KOTA BATU - Aldy Candra Andriyansa; Ach. Faisol; Devi Wahyu Ertanti (VICRATINA, 2021)
In this study, researcher focus on the role of PC IPNU city Batu to develop organizational interest based on the value “Aswaja An-Nahdliyah” in Mts Hasyim Asary. Reseaecher use qualitative methods. Data collection prosedure is using interviews, observations, and documentation. The result of this study is to develop organizational interest based on the value "Aswaja an-nahdliyah" in Mts Hasyim Asary. The role of PC IPNU is holding makesta (member loyalty period) activity. In this makesta will be filled with many kinds of materials such as leadership, about NU itself, organization, and youth digital loteration movement. With this activities, researcher hope that organizational interest will be improved for students who understand "ahlisunnah waljamaah an-nahdliyah"